The Influence of Peer Groups and Fear of Missing Out (FOMO) on Skincare Purchasing Decisions Among Generation Alpha, with Product Reviews as a Mediating Variable - Naily Mey Sofiyyun Nida; Mohamad Rifqy Roosdhani (Jurnal Economic Resource, 2026)
This study aims to determine the influence of peer groups and Fomo on Skincare purchasing decisions among the Alpha generation in Jepara, with Product Reviews as a mediating variable. This study uses a quantitative approach with Partial Least Square (PLS) data analysis techniques to test the relationship between variables. The population in this study consisted of skincare users in Jepara aged 9-14 years. Data were collected through an online questionnaire using Google Forms, resulting in 170 respondents selected using the Ferdinand formula. The research instrument used a Likert scale ranging from 1 to 10. The results showed that peer groups and Fomo have a positive and significant influence on Product Reviews and purchasing decisions. Furthermore, Product Reviews were proven to mediate the influence of peer groups and Fomo on Skincare purchasing decisions among the Alpha generation.